2021
DOI: 10.30684/etj.v39i3a.1894
|View full text |Cite
|
Sign up to set email alerts
|

Al2O3-TiO2-PMMA Bio-Composite Coating Via Electrostatic Spray Technique

Abstract: This work aims preparation of polymer-based biocomposite coating by electrostatic spray method onto 316L stainless steel substrate, the present work will compare the effects of incorporation of Al2O3 and TiO2 particles at a different percentage of (10,15 and 20 % wt. from Al2O3 and TiO2 with (90,85 and 80% wt. PMMA - based electrostatic deposition coating is studied. The structure and chemical composition of composite coatings were studied by using (SEM) & (EDS) and mechanical properties (Microhardness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…Therefore, this study attempts to increase the alloy's resistance against corrosion while maintaining its good mechanical properties by applying a modified coating layer of PMMA-based composites titanium carbide as reinforcement material using dry electrostatic spray deposition (ESD) under constant conditions (25 kV, 15-20 cm distance, compressed air of 15 psi, and spraying angle about 45.0o for 3 0sec). The titanium carbide was added with ratios of (5,10,15,20) wt. % respectively.…”
Section: H I G H L I G H T S Abstractmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this study attempts to increase the alloy's resistance against corrosion while maintaining its good mechanical properties by applying a modified coating layer of PMMA-based composites titanium carbide as reinforcement material using dry electrostatic spray deposition (ESD) under constant conditions (25 kV, 15-20 cm distance, compressed air of 15 psi, and spraying angle about 45.0o for 3 0sec). The titanium carbide was added with ratios of (5,10,15,20) wt. % respectively.…”
Section: H I G H L I G H T S Abstractmentioning
confidence: 99%
“…They found that HA with 3% SiC coating gives the optimized requirements, with a low micro-cracks level compared with other coatings [9]. In 2021, Issa et al fabricated a thin film of PMMA-based composite coating with various bio-ceramic materials as reinforcements using an electrostatic deposition [10]. FESEM & EDS were used to study the surface morphology; the coating hardness and adhesion were studied using mechanical tests.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis through scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX) revealed robust adhesion and enhanced performance in biological environments, simulated through the utilization of simulated body fluid (SBF). Issa et al [ 16 ] deposited a thin layer of poly methyl methacrylate (PMMA) reinforced with diverse bioceramics onto a stainless-steel substrate using electrostatic deposition. The resulting coating exhibited homogeneity, without any signs of cracking, and demonstrated satisfactory mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Electrostatic spray deposition (ESD) has however lately gained interest as a "solvent-free dry-powder coating technology" for implants. Fast deposition time, energy savings, and a significant reduction in operating costs are just a few of the reasons why ESD has gained interest over alternative powder deposition technologies [15,16,17].…”
Section: Introductionmentioning
confidence: 99%